Behavior Therapy Application by Relaxation Method to Overcome Children Aggressiveness - Deliana, Sri Maryati; Haryadi, Sugeng; Budiningsih, Tri Esti (Indonesian Journal of Early Childhood Education Studies, 2016)
This research is measuring as well as explaining the children’s aggressive behavior in Pembina kindergarten. The researcher conducted behavioral therapy by using relaxation method to overcome that aggressive behavior. Applying mixed research methods of qualitative and quantitative by using pre-experiment one shot case study design, it was found that relaxation therapy data have not been optimal yet to reduce the subjects’ aggressiveness level. Hence the existence of important family factor should be included in the children’s therapy process. Relaxation therapy should be balanced with family therapy, due to subjects’ aggressiveness factor is a form of subjects’ protest to their family.